International evidence on understanding the determinants of crime - Abdul Hamid, Baharom (2012)
This study was conducted to investigate the relationship between crime and economic variables such as income, unemployment, inflation, interest rate, and also the political violence, both domestic and regional. The main motivation of the study was to have a better understanding of crime, finding and suggesting alternative way of approaching crime. We analyzed 21 countries, with data spanning from 1960 to 2001.We started our study on this objective by adapting the model and framework that was introduced by Viren (2001) based on Becker (1968), Block and Heineke (1975) and we made slight modification by rephrasing it in order to not only capture the long run relationship but also the short run adjustment. We employed panel-error-correction based cointegration (Persyn and Westerlund (2008)) to analyze and estimate the model. A number of important findings were extracted from the analysis in accordance to the objectives of this study. Firstly, it determines the negative long run relationship between income and crime, ,positive long run relationship between inflation and crime, unemployment and crime as well as lending rate and crime. As for the political violence variable, domestic political violence seems to be negatively related; on the contrary regional political violence is positively related. We believe this might be attributed to the spillover effect. All these signs are as anticipated and justified in this study and are concurrent with most of the past literatures.